Evaluation of PV, Wind, Diesel Hybrid Energy Potential for GSM Tower in Myanmar - Zin Mar Nyo (International Journal of Electrical and Computer Engineering (IJECE), 2015)
Not only GSM, WCDMA but also CDMA technology can be used in Myanmar but GSM pre-dominates in the market. There are over million unique subscribers across the country in 2013. Power supply for telecom becomes main challenges in Myanmar where the electricity can not access in rural area. To minimize deficit of power, the government has set a target to covert some of tower sites to renewable solutions by 2015. This paper proposes the use of a PV, wind and diesel generator hybrid system with storage element in order to determine the optimal configuration of renewable energy in Myanmar.  This paper discusses the development of a renewable energy sources (RES)  that  can  be  used  for  electric  power  supply  of  GSM  base  station  site  at  any  given  time and  considers  the  feasibility  of  developing  Solar  (photovoltaic)-Wind-Diesel  hybrid power  systems  for  supplying  electricity  to  off-grid  rural telecommunication.  The Hybrid Optimization Model for Electric Renewables (HOMER) was used  to  simulate  and  generate  feasible  solution  through  combinations of photovoltaic, Wind Turbines and Diesel  Generator with  a  minimum  levelised  cost  of  electricity supply and to  determine  the  technical feasibility of the system.